Ecotheology Nuances in Tafsir al-Miṣbah: Alternative Solutions to Environmental Problems in Indonesia - Ali, Rijal; Rahmatina, Nada; Abdillah, Muhammad Torieq (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
Ecotheology Nuances in Tafsir al-Miṣbah: Alternative Solutions to Environmental Problems in Indonesia. Environmental issues are crucial because they affect everyone. The involvement of religion (theology) in environmental issues is certainly very influential in the religious community of Nusantara. This study aims to present eco-theological nuances in the interpretation (tafsir) of Nusantara. This article focuses on Tafsir al-Miṣbah by M. Quraish Shihab, which is considered more relevant to the modern context and can be used as a representative of the Nusantara interpretation. Using the literature study method with a descriptive analysis approach, this study concludes that according to M. Quraish Shihab, environmental damage cannot be separated from the human spiritual crisis. The universe and all its contents are interrelated and influence each other, rely on, and return to Allah Swt. Human disobedience causes the universe imbalances. The characteristics of nifâq, kufr, zhalim and hubb al-dunyâ resulted in a dull sensitivity to the environment and gave birth to a blind ambition without regard for preserving nature. On the other hand, environmental preservation goes hand in hand with monotheism because monotheism is the basic pillar of earth management. Tauhid will raise awareness so as not to act arbitrarily to nature. On the other hand, environmental preservation goes hand in hand with monotheism because monotheism is a fundamental pillar of managing the earth. Tawhid will raise awareness so as not to act arbitrarily against nature. When related to the Indonesian context, M. Quraish Shihab provides tolerance if environmental damage occurs due to earth management activities, as long as the person concerned always asks for forgiveness and Allah’s mercy.Dewasa ini, lingkungan menjadi isu yang krusial karena berdampak bagi semua orang. Keterlibatan agama (teologi) dalam isu lingkungan tentunya sangat berpengaruh dengan masyarakat Nusantara yang religius. Penelitian ini bertujuan menampilkan nuansa ekoteologi dalam tafsir Nusantara. Untuk memfokuskan penelitian, artikel ini hanya membatasi pada Tafsir al-Miṣbah karya M. Quraish Shihab yang dianggap lebih relevan dengan konteks saat ini dan dapat dijadikan salah satu representatif dari tafsir Nusantara yang populer di kalangan masyarakat Indonesia. Menggunakan metode studi pustaka dengan pendekatan analisis deskriptif, penelitian ini menyimpulkan bahwa menurut M. Quraish Shihab, kerusakan lingkungan tidak dapat dipisahkan dari krisis spiritual manusia. Alam raya dan segala isinya saling berkaitan dan saling mempengaruhi satu sama lain serta bertumpu dan kembali kepada Allah Swt. Kedurhakaan manusia mengakibatkan gangguan keseimbangan alam raya. Sifat nifâq, kufur, zhalim, dan hubb ad-dunyâ mengakibatkan tumpulnya kepekaan terhadap lingkungan dan melahirkan ambisi buta tanpa menghiraukan kelestarian alam. Sebaliknya, pelestarian lingkungan berjalan beriringan dengan ketauhidan karena tauhid merupakan tonggak dasar pengelolaan bumi. Tauhid akan menimbulkan kesadaran agar tidak berlaku sewenang-wenang terhadap alam. Jika dikaitkan dengan konteks ke-Indonesia-an, M. Quraish Shihab memberikan toleransi bahwa jika terkadang terjadi kerusakan lingkungan akibat adanya aktivitas pengelolaan bumi, selama yang bersangkutan senantiasa meminta ampun dan memohon rahmat Allah.